Δακτυλογραφημένη επιστολή του Γεν.Γραμματέα πανεμπορικής ένωσης Ελλάδος προς τον Εμπορικό Σύλλογο Κοζάνης
Δακτυλογραφημένη επιστολή του Γεν.Γραμματέα πανεμπορικής ένωσης Ελλάδος προς τον Εμπορικό Σύλλογο Κοζάνης.